1994
DOI: 10.1136/oem.51.9.579
|View full text |Cite
|
Sign up to set email alerts
|

Work related symptoms, sensitisation, and estimated exposure in workers not previously exposed to flour.

Abstract: Findings are presented from the initial cross sectional phase of a cohort study of employees exposed to flour in bakeries or mills. Of 401 eligible workers in seven sites 344 (86%) were surveyed; symptoms assessed by self completed questionnaire, and sensitisation measured by the response to skin prick tests, were related to intensity of exposure both to total dust and to flour aeroallergen. Among 264 subjects without previous occupational exposure to flour, work related symptoms which started after first empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
5
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 8 publications
12
92
5
3
Order By: Relevance
“…The prevalence of sensitization to enzymes was comparatively high, 12-13%. Prevalences of 5% to 40% (in heavily exposed groups) were reported in the detergent industry in the early 1970s (2), and recent studies have found rates of 5-8% in bakeries (6,7,12). Enzyme sensitization was the most common towards cellulase and xylanase, being the main products of the plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of sensitization to enzymes was comparatively high, 12-13%. Prevalences of 5% to 40% (in heavily exposed groups) were reported in the detergent industry in the early 1970s (2), and recent studies have found rates of 5-8% in bakeries (6,7,12). Enzyme sensitization was the most common towards cellulase and xylanase, being the main products of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…With improvements in industrial hygiene the proble~n abated (2). Later on, with the increased production and use of new enzymes since the 1980s (3,4), allergies have emerged in other industries, too, especially in bakeries to fungal (Aspergillus oryzae, Aspergillus rziger) alpha-amylase (4)(5)(6)(7). Some reports of allergies in laboratories and pharmaceutical companies have also been published.…”
mentioning
confidence: 99%
“…Other organizations, such as the Health and Safety Executive (HSE) in the United Kingdom and the Nordic Expert Group, favored a different approach, for which the rationale has been described earlier (4,5). The standard-setting process is complicated because only a few studies have dealt in any detail with exposure among bakers and sensitization, mainly because such data were not available until recently (6)(7)(8)(9). Moreover, the shape of the relationship has not been studied in depth in most earlier studies.…”
mentioning
confidence: 99%
“…A variety respiratory effects have been described among bakers, including asthma, chronic obstructive pulmonary disease (COPD), impairment of pulmonary function, etc [1][2][3][4][5]. Bakers' asthma represents the first cause of occupational asthma in France and one of the most current etiologies in countries of Western Europe [6,7].…”
Section: Introductionmentioning
confidence: 99%